2019
DOI: 10.3390/cancers11010087
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention and Therapy of Two Types of Gap Junctional Intercellular Communication–Deficient “Cancer Stem Cell”

Abstract: Early observations showed a lack of growth control and terminal differentiation with a lack of gap junctional intercellular communication (GJIC). Subsequent observations showed that epigenetic tumor promoters and activated oncogenes, which block gap junction function, provide insights into the multi-stage, multi-mechanism carcinogenic process. With the isolation of embryonic induced pluri-potent stem cells and organ-specific adult stem cells, gap junctions were linked to early development. While tumors and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 115 publications
(146 reference statements)
1
12
0
Order By: Relevance
“…The impact of non-communicating Cx26 on the malignant potential of BCSCs allows the expansion of the classical view on connexin function in CSCs. This is in line with a recent review by Trosko, which provides the characterization of cancer stem cells in view of connexin expression: He states that expression of the transcription factor OCT4A, which has been associated with the pluripotency of stem cells [118], is also a characteristic of CSCs, and that those pluripotent CSCs expressing OCT4A do not express connexins and do not form functional gap junctions [112]. In contrast, in those CSCs expressing connexin proteins, these do not form functional gap junctions but serve a communication-independent purpose—which is supported by the data on Cx26 in breast cancer CSCs as outlined above.…”
Section: Connexins In Cancer Stem Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…The impact of non-communicating Cx26 on the malignant potential of BCSCs allows the expansion of the classical view on connexin function in CSCs. This is in line with a recent review by Trosko, which provides the characterization of cancer stem cells in view of connexin expression: He states that expression of the transcription factor OCT4A, which has been associated with the pluripotency of stem cells [118], is also a characteristic of CSCs, and that those pluripotent CSCs expressing OCT4A do not express connexins and do not form functional gap junctions [112]. In contrast, in those CSCs expressing connexin proteins, these do not form functional gap junctions but serve a communication-independent purpose—which is supported by the data on Cx26 in breast cancer CSCs as outlined above.…”
Section: Connexins In Cancer Stem Cellssupporting
confidence: 81%
“…When referring to CSCs in terms of a tumor-transmitting cell with self-renewal capacity, irrespective of their pluripotency, the expression of connexins has been demonstrated by many studies and was shown to have a functional impact—despite the connexins themselves possibly being dysfunctional [112]. In general, CSCs depend on intercellular communication, (a) via paracrine secretion of, for example, interleukins, cytokines or pro-angiogenic factors [113,114,115] and (b) via gap junctional intercellular communication.…”
Section: Connexins In Cancer Stem Cellsmentioning
confidence: 99%
“…These kinds of studies must now be put into the context of knowing all tumours are a mixture of “cancer stem cells” and “cancer non-stem cells”. It is the “cancer stem cells” that must be targeted in order to prevent them from sustaining the growth of the tumour [28].…”
Section: Introductionmentioning
confidence: 99%
“…Several phytochemicals are able to induce apoptosis in cancer cells by enhancing gap-junctional intercellular communication (GJIC) [30,31,32,33,34]. Cancer cells usually exhibit dysfunctional GJIC, due generally to the lack of expression of connexin genes or the aberrant localization of connexin proteins [28,35], the structural components of the hexameric hemichannels that, when juxtaposed on adjacent cells, build up intercellular gap junctions [36]. As the tumour promoter agents exert their action by affecting cell-cell communication [37,38], several natural compounds, such as phytochemicals able to restore or enhance GJIC, although transiently, are able to allow cell-cell coupling and induce apoptosis through the passage of chemical signals [30,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Gap junctions facilitate intercellular communication and regulate proliferation and differentiation [1]. Since gap junctional intercellular communication (GJIC) is necessary to mediate contact inhibition in growing cells and tissues, inhibited GJIC might reduce growth control and differentiation [2] and is a hallmark of epithelial-derived cancer cells [3]. James Trosko stated that epigenetic tumor promoters and activated oncogenes can block gap junction function and yield insights into the complex [2].…”
Section: Introductionmentioning
confidence: 99%